Honeybee Products and Apitherapy - Sibel Silici (Turkish Journal of Agriculture: Food Science and Technology)
Honey is the most known among the honeybee products. But apart from honey, there are other bee products that are nutritious and supportive of treatment. Pollen, royal jelly, and propolis are among the bee products that have the highest number of researches made in the last years. However, products such as bee bread (perga) and drone larvae (apilarnil) are very unknown products with little work. Apitherapy; bee and bee products as a method of complementary application in the protection and treatment of certain diseases. However, in order for these applications to be successful, the chemical and biological properties of these products need to be known. For this purpose, the definition, chemical and biological properties and therapeutic activities of bee products are included in this study.